Postmortem Neurochemistry Shows High Dopamine Levels in Brain of Cocaine Consumers - Virginia M Carvalho; André R Fukushima; Luiz R Fontes; Jorge C Florio; Alice AM Chasin (Forensic Science Today - Peertechz Publications, 2016)
Cocaine abuse represents a serious problem to many countries and is frequently related to deaths. Differences in response, drug tolerance, drug sensitization and postmortem redistribution diffi cult clarifying cocaine related deaths. Thus, additional parameters associated to cocaine exposition could assist the pathologist in interpreting the deaths cases. In order to verify whether the cocaine action mechanism indicates a postmortem biochemical profi le, dopamine and serotonin levels were quantifi ed in brain samples. Two groups were established, one composed by cocaine consumers and other composed by non-cocaine consumers. Levels of dopamine and its metabolites were higher in basal ganglia of cocaine consumers group, but the concentrations were weakly correlated with cocaine concentrations in brain and in whole blood. Although catecholamine at autopsy may show considerable variations due to various factors, the high dopamine and metabolites levels can be associated with the cocaine action mechanism which is based on increased of dopamine levels in dopaminergic pathways in the central nervous system.